Participation in Education: from theory to practice - Zaitegi de Miguel, Nélida (Avances en Supervisión Educativa, 2020)
The need for the voice of the educational community in education is unquestionable and it has given rise to much literature and less research than necessary to know the phenomenon in all its complexity. Although "paralysis through analysis" is common, this time we have chosen to start participatory processes and learn from them through practice.Approaching participatory processes demands the conviction that they are necessary and possible, that the educational community is capable, putting the means to it, of making risky decisions and of assuming the consequences, in the exercise of a democratic and mature citizenship.Counting on the students, if they are allowed and taught how to participate, the families with updated tools to make their voices heard, the teachers as a fundamental agent in the educational process, and the city councils. All of them are called to build the necessary social fabric to transform education and put it in the 21st century once and for all.
Keywords: participation; democratic governance; transparency; social innovation; co-responsibility; collective commitment; school council